[Ru(phen)2dppz]2+ luminescence reveals nanoscale variation of polarity in the cyclodextrin cavity. Issue 9 (17th December 2015) - Higgs, P. L.; McKinley, A. W.; Tuite, E. M.
Abstract : Insertion of dppz with phosphorylated β-cyclodextrin results in multi-exponential [Ru(phen)2 dppz] 2+ emission; binding is weaker than [Ru(phen)3 ] 2+, but shows stereoselectivity. Abstract : Phosphorylation of β-cyclodextrin enhances binding with Ru(ii )polypyridyl complexes, and promotes selectivity based on chirality and ligand hydrophobicity. For [Ru(phen)2 dppz] 2+, inclusion of dppz results in a dramatic increase in luminescence with multiple lifetimes. The sensitive response of photophysics to the environment reveals nanoscale variation of polarity.